Analisis Determinan PAD Sub Sektor Pariwisata di DIY Periode 2012-2017 - Afifah Tessa Sekar N; Rifki Khoirudin (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2019)
This study aims to find out what factors influence Regional Revenue in the tourism sub-sector in DIY Province, especially cities / districts from 2012-2017. In this study the variables used are the Regional Original Revenue of the Tourism Sub Sector as the dependent variable, the independent variable is the number of tourist visits, the number of tourist objects, the number of the hotels, the number of tourist travel agencies. This research uses panel data method, which is a combination of time series, in the form of time series from 2012-2017 and cross section data in the form of latitude sequences of 5 cities / districts in DIY Province, with a total number of observation of 30 observation. The result showed that the variabel number of tourists and the number of hotels had a positive and significant effect on the Regional Original Revenue of the tourism sub-sector, while the number of tourist objects and the number of tourist travel agencies did not significantly influence the Regional Revenue of the tourism sub-sector in DIY Province.